2020
DOI: 10.3390/mi11090845
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Mechanophenotyping in Microfluidics to Evaluate Behavior of U87 Glioma Cells

Abstract: Integration of microfabricated, single-cell resolution and traditional, population-level biological assays will be the future of modern techniques in biology that will enroll in the evolution of biology into a precision scientific discipline. In this study, we developed a microfabricated cell culture platform to investigate the indirect influence of macrophages on glioma cell behavior. We quantified proliferation, morphology, motility, migration, and deformation properties of glioma cells at single-cell level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…A precise and accurate characterization of cells in the GBM microenvironment will lead better diagnosis, prognosis, and personalized treatment strategies [9][10][11][12][13]. In literature, there is still a lack of quantification about electrical and mechanical properties of glioma cells at single-cell level [16,19,27,[29][30][31]. In this context, Memmel and co-workers reported the migration pattern, actin cytoskeleton organization, and response to PI1K-, mTOR-, and Hsp90-inhibition of glioblastoma cells with different invasive capacities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A precise and accurate characterization of cells in the GBM microenvironment will lead better diagnosis, prognosis, and personalized treatment strategies [9][10][11][12][13]. In literature, there is still a lack of quantification about electrical and mechanical properties of glioma cells at single-cell level [16,19,27,[29][30][31]. In this context, Memmel and co-workers reported the migration pattern, actin cytoskeleton organization, and response to PI1K-, mTOR-, and Hsp90-inhibition of glioblastoma cells with different invasive capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated effective tools to investigate mostly mechanical properties of glioma cells using fluorescence microscopy [15][16][17][18][19][20][21][22][23][24][25][26][27], 2-photon imaging [11,28], atomic force microscopy [16,29,30], single-cell force spectroscopy [16], and microfluidic technologies [31][32][33][34][35][36][37][38][39]. In contrast to mechanical features, electrical properties of glioma cells have not been extensively interrogated.…”
Section: Introductionmentioning
confidence: 99%
“…Unique mechanical properties of glioma and its microenvironment provide a basis for the development of novel diagnostics to address two unmet needs in clinical medicine: 1) accurate identification of infiltrative disease in nervous tissue that is radiographically and microscopically occult and 2) characterization disease heterogeneity and plasticity towards predictive analytics for treatment response or prognosis. Fundamental technologies are available as were described in the studies presented in this review such as MRE and other tools for rheological phenotyping, and these have the potential to be adapted and refined as possible intraoperative adjuncts or as supplements to the conventional imaging obtained for patients with GBM to better guide treatment choices (57,59,61,62,67,(152)(153)(154). Briefly, techniques can be categorized based on the substrate assessed-either cells and tissue or more macroscopically a region of the brain (Table 2).…”
Section: Diagnosticsmentioning
confidence: 99%
“…Comprehensive reviews of methodologies used to study mechanical properties in vitro and in vivo can be found elsewhere (47,85,155). Advances in bioengineering in the fields of microfluidics, biomimetics, and hydrogel may also enable the development of high-throughput, point-of-care methods to define disease features such as the mechanophenotype that may aid in clinical-decision making (84,147,152,157).…”
Section: Diagnosticsmentioning
confidence: 99%
“…The same group [ 33 ] investigated the impact of macrophages on glioma cell behavior by using a microfabricated cell culture platform. They quantified motility, migration, morphology, proliferation, and deformation characteristics of glioma U87 cells at the single-cell resolution to unveil biomechanical heterogeneity.…”
mentioning
confidence: 99%